Greening of science: main vectors of the problem - Lepskaya, Nelly D. (Journal of the Belarusian State University. Ecology, 2019)
Understanding the harm done to the environment by human activities, threats to human existence led to the realization of the role of ecological knowledge and the inevitable greening of science.
Keywords: greening the science; environment; biosphere; ecological system; ecological consciousness; ecological education; ecological culture; ecological activity